AGENDA MEDIA MENGENAI PILPRES PEMILU 2014: Analisis Isi Terhadap Pemberitaan Mengenai Setatus Pencalonan Jokowi Dalam Surat Kabar Kompas. - Priyadi, Catur (Universitas Prof. Dr. Moestopo (Beragama), 2014)
The momentum of presidential election as a political reality of course a lot of attention from various circles to be observed and assessed by the PR. the media agenda and the theoretical approach using content analysis methodology with a quantitative approach to the Kompas newspaper, because it basically is one of the various methods that are categorized as Unobtructive Research, is the possible research methods the researcher to be able to study the process of social life is not directly without causing change existing data. This study aims to gain an idea of how the media view or highlight cases Jokowi nomination as a Presidential candidate in the 2014 Kompas Newspaper. Positivist research paradigm developing studies of media effects, in addition to the positivist paradigm also emphasizes objectivity that world phenomenon can be explained by the laws of the objective, rational, and can be tested. With the quantitative approach Agenda media measured by content analysis technique based on the category dikoding existing issues, measured by the frequency and volume issues trigger issues (Centimeter Area newspaper column), test reliability or consistency of the formula Ole R. Holsty. Here the researchers conducted a pretest with mengkoding way categorization of the test sample into the inter-code. From the data processing aspects of the audience for the results of the salience, theres findings that the news in the newspaper Kompas that is relevant to the cases candidacy in the 2014 presidential election results Jokowi test analysis of the aspects the audience salience (level of relevance eversion news for audiences with news content the needs of the audience) indicates that there is a significant relationship between the loading time news before and after campaign with the information needed audiences. Audience salience Relevance news content in terms of the need for public information associated with the loading time news (X = 11,3,1 df, p 0.05). From the data processing to result in the aspect Velence / valence (pleasant or unpleasant news for the audience), the findings indicate that the newspapers about the case Nominations Jokowi compass on the 2014 presidential election is not fun, it is seen from news reports about personal image Jokowi when served as Governor of Jakarta. Valence Serving humanity Jokowi news connected with the loading time (X = 18.1 df, p 0.05).